Pancasila as The Foundation of The State in The Perspective of The Democratic State of Law's Ideals - Okliyani, Windicha; Maharani, Septia Riska; Ihsan, Muhammad Aufal; Sari, Lusi Puspika (Universitas Tidar, 2023)
Pancasila is the foundation and ideology of the Indonesian state that has become the foundation in developing a democratic legal system. Pancasila becomes the basis of the Indonesian legal ideals as a democratic state because it contains values that are in line with the principles of democracy. As the basis of legal ideals, Pancasila has a central role in composing a legal system that guides the direction and principles in carrying out a just, democratic, and law- based governance. The values contained in Pancasila, such as social justice, just and civilized humanity, democracy, and popular sovereignty, become the basis for the formation of laws and public policies.In practice, Pancasila serves as a source of law in the process of making public policies and stipulating laws in Indonesia. Pancasila values also serve as a reference in law enforcement, where judges' decisions and public policies must be in line with Pancasila values. Pancasila also has an important role in maintaining the unity and unity of the Indonesian nation. Pancasila values, such as Bhinneka Tunggal Ika, become the basis for building a strong and robust unity in Indonesian society, so that a just, democratic, and sovereign state can be realized, thus creating a prosperous and harmonious society.